Identification of Somatic Mutations in Dementia-related Genes in Cancer Patients - Kim, Yong-Chan; Jeong, Byung-Hoon (Current Alzheimer Research, 2020)
Background: Dementia is an overall term of brain diseases, including Alzheimer’s disease (AD), tauopathies and synucleinopathies. To date, somatic mutations in dementia-related genes, including the amyloid precursor protein (APP) gene, presenilin 1 (PSEN1) gene, PSEN2 gene, microtubule- associated protein tau (MAPT) gene, alpha-synuclein (SNCA) gene and leucine-rich repeat kinase 2 (LRRK2) gene, have been considered one cause of dementia. We have questioned the impact of somatic mutations in dementia-related genes on cancer. Methods: In the present study, we investigated somatic mutations in the APP, PSEN1, PSEN2, MAPT, SNCA and LRRK2 genes and the impact of these somatic mutations. Results: From The Cancer Genome Atlas (TCGA) database, we found 1,643 somatic mutations in the APP, PSEN1, PSEN2, MAPT, SNCA and LRRK2 genes in cancer patients. Strikingly, compared to the distributions of cancer types in total cancer patients, somatic mutations in the dementia-related genes showed an extremely low distribution in glioblastoma patients. Conclusion: To the best of our knowledge, this is the first investigation of dementia-related genes in cancer patients.
Keywords: PSEN1